1996
DOI: 10.1103/physrevb.54.4021
|View full text |Cite
|
Sign up to set email alerts
|

Theory of commensurable magnetic structures in holmium

Abstract: The tendency for the period of the helically ordered moments in holmium to lock into values which are commensurable with the lattice is studied theoretically as a function of temperature and magnetic field. The commensurable effects are derived in the mean-field approximation from numerical calculations of the free energy of various commensurable structures, and the results are compared with the extensive experimental evidence collected during the last ten years on the magnetic structures in holmium. In genera… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0
4

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 58 publications
(108 reference statements)
3
21
0
4
Order By: Relevance
“…It has previously turned out to be of great value to assist the analysis of diffraction experiments by theoretical model calculations of the stability of the structures which may occur. [15][16][17] The method consists in calculating the free energies of different commensurable structures within the mean-field approximation, by the application of a straightforward iteration procedure. The results are compared to each other and thereby the most stable structure may be identified.…”
Section: Mean-field Model Of the Magnetic Structuresmentioning
confidence: 99%
“…It has previously turned out to be of great value to assist the analysis of diffraction experiments by theoretical model calculations of the stability of the structures which may occur. [15][16][17] The method consists in calculating the free energies of different commensurable structures within the mean-field approximation, by the application of a straightforward iteration procedure. The results are compared to each other and thereby the most stable structure may be identified.…”
Section: Mean-field Model Of the Magnetic Structuresmentioning
confidence: 99%
“…Similar to the Dy, the moments in Ho are ferromagnetically coupled within the basal (ab)-plane, but their orientation rotates at a certain angle while moving along the c-axis. It was, however, shown that, contrary to the Dy, the magnetic order in bulk Ho is strongly affected by the crystal-field anisotropy [6,14,15]. The magnetic moments is bunching along the six easy axes in the basal plane due to the crystal-field anisotropy, what leads, firstly, to the lockin of the wave vector into values commensurable with the atomic lattice in certain temperature intervals, and, secondly, to the formation of a series of long period commensurate spin-slip structures [6,14,15].…”
Section: Pacs Numbersmentioning
confidence: 99%
“…9,12 The only crystal-field terms allowed for the hcp structure have lϭ2, 4, 6 and mϭ0 and l ϭmϭ6. The Heisenberg exchange and the dipolar coupling are both two-ion interactions.…”
Section: Theoretical Modelmentioning
confidence: 99%